Intra-rater and inter-rater reliability of ultrasonographic measurements of acromion-greater tuberosity distance in patients with post-stroke hemiplegia. Issue 3 (2nd April 2016) - Kumar, Praveen; Cruziah, Reynold; Bradley, Michael; Gray, Selena; Swinkels, Annette
Abstract : Background: Glenohumeral subluxation (GHS) is reported in up to 81% of patients with stroke. Ultrasonographic measurements of GHS by measuring the acromion-greater tuberosity (AGT) have been found to be reliable for experienced raters. Objectives:The primary aim was to assess the intra-rater reliability of measurements of AGT distance in people with stroke following a short course of rater training. A secondary aim was to compare the inter-rater reliability of these measurements between novice and experienced raters. Methods:Patients with stroke ( n = 16; 5 men, 11 women; 74 ± 10 years) with 1-sided weakness who gave informed consent were recruited. Ultrasonographic measurements were recorded at the bedside by two physiotherapists with patients seated upright in a hospital chair. Reliability was assessed by intra-class correlation coefficients (ICCs) and the standard error of measurements (SEM). Minimum detectable change (MDC90) scores were used to estimate the magnitude of change that is likely to exceed measurement error. Results:Mean ± SD AGT distances on the affected and unaffected sides for rater 1 were 2.2 ± 0.7 and 1.7 ± 0.4 cm, respectively. Corresponding values for rater 2 were 2.5 ± 0.6 and 2.0 ± 0.4 cm. Intra-class correlation coefficient values for the affected and unaffected shoulders for rater 1 were 0.96 and 0.91, respectively. Corresponding values for rater 2 were 0.95 and 0.90.SEM and MDC90 for both affected and unaffected shoulders were ≤ 0.2 cm. Inter-rater reliability coefficients were 0.86 (affected) and 0.76 (unaffected) shoulders. Conclusion:Ultrasonographic measurement of AGT distance demonstrates excellent intra-rater reliability for a novice rater. Inter-rater reliability of ultrasonographic measurement of AGT also demonstrates good reliability between novice and experienced raters.